Prevalence of refractive error and attitude towards spectacles wear among car drivers in UiTM Puncak Alam / Nazirul Hariez Abdul Wahab - Abdul Wahab, Nazirul Hariez (2015)
Purpose: The study purpose was to find out the proportion of the car driver having the refractive error either fully corrected refractive error or uncorrected refractive error and also their attitude towards spectacles wearing while driving. Methods: Data was analysed and displayed in percentage and frequency using descriptive analysis. A Chi Square association test was also done to find the association between refractive error correction and visual difficulty at distance. Results: Almost half of the participants have reduced visual acuity at distance but are still driving. There was also positive association between refractive error correction and visual difficulty at distance with p = 0.005. Forty percent of these drivers did not wear spectacles while driving due to inconvenience of spectacles, uncomfortable of wearing spectacle and vision obstructed by the spectacles' frame. Conclusion: Car drivers with reduced habitual distance visual acuity were more likely to have visual difficulty at distance especially in myopic individuals. Some of these drivers were not wearing any spectacles despite having uncorrected refractive error, which most of them claimed of uncomfortable of wearing spectacles and obstructed vision due to spectacles frame.